SUSTAINABLE DEVELOPMENT OF THE FARMERS COOPERATIVE SYSTEM IN AP VOJVODINA - Ševarlić, Miladin; Raičević, Vuk; Glomazić, Rade (Economics of Agriculture, 2012)
On the basis of the systematization of relevant attitudes predominant today with respect to sustainability at the global level, the authors have made a concept of a questionnaire, carried out a survey and paper-presented the results of their research into the attitudes of directors of farmers cooperatives regarding the socio-economic, legal and ecological aspects of the sustainability of the cooperatives system as "the third sector" of the economy and rural areas in the Autonomous Province of Vojvodina, with a reference to the legal, economic and ecological ambience of business doing performed by cooperatives and other enterprises in the Republic of Serbia – with a special reference to obligations which, when sustainability is concerned, emerge from the need for harmonizing with the European Unions legislation.